Auditors Under Fire: The Association Between Audit Errors and the Career Setbacks of Individual Auditors - CHEN, KEVIN C. W.; CHEN, TAI‐YUAN; HAN, WEIFANG; YUAN, HONGQI (Journal of Accounting Research, 2022)
ABSTRACT This paper examines whether and how individual auditors are disciplined for audit errors. Taking advantage of the long history of auditor identity data from China, we find that signing auditors with client restatements are likely to lose the privilege of signing the audit reports of public clients. However, auditors can avoid this consequence by issuing a modified audit opinion to warn of the potential misstatement. We show that auditors are more likely to be disciplined when their firms operate in less concentrated audit markets. Finally, we find positive outcomes from the disciplinary action of the audit firms. Firms that discipline their auditors for restatements have a larger decrease in the rate of client restatements and a larger increase in market share, compared to nondisciplining firms. Their clients have a higher earnings response coefficient after the disciplinary action. In summary, our results suggest that individual auditors in China can face career setbacks when they produce poor quality audits.